The Concept of Intercession According to Shaykh Salih Al-Fawzan’s Contemporary Interpretation and Its Influence on the Strengthening of theological Education - Cahyo, Luthfi Dwi; Hamdani, Moch. Choirul; Kadiatmaja, Agung Pranoto (Universitas Muhammadiyah Prof Dr Hamka, 2025)
This study aims to analyze the concept of intercession (shafā‘ah) according to Shaykh Ṣāliḥ al-Fawzān, focusing on its classification, normative basis, and relevance in contemporary Islamic theology. The research employed a qualitative descriptive approach through library research, with primary sources including al-Fawzān’s works, Qur’anic verses, and authentic hadiths, and secondary sources comprising national and international academic literature. Data were analyzed using content and thematic analysis to identify key concepts, arguments, and patterns of thought. The findings indicate that al-Fawzān defines intercession as a supplication by a creature to Allah to grant benefit or avert harm for others, requiring two main conditions: Allah’s permission for the intercessor and Allah’s approval for the recipient. Intercession is classified into two categories: al-shafā‘ah al-muthbatah (affirmed intercession) and al-shafā‘ah al-manfiyyah (rejected intercession), consistent with the views of classical scholars and modern theological literature. These findings emphasize that a correct understanding of intercession supports the purification of tawhid and prevents doctrinal deviation. The study also suggests further comparative research across Islamic schools of thought and the integration of al-Fawzān’s perspectives into modern tauhid education.